Crack‐tip blunting and its implications on fracture of soft materials. Issue 4 (21st January 2023) - Spagnoli, Andrea; Brighenti, Roberto; Montanari, Matteo; Terzano, Michele
Abstract: Fracture of compliant materials is preceded by large deformations that reshape initially sharp cracks into rounded defects. This phenomenon, known as elastic crack blunting, is peculiar of rubber‐like polymers and soft biological tissues, such as skin, vessel walls, and tendons. With this work, we aim to provide a discussion on crack‐tip blunting and its implications in terms of tearing resistance and flaw tolerance of soft elastic materials. The characteristic features of the crack‐tip zone in the framework of nonlinear elasticity are reviewed analytically and with the help of finite element analyses on pure shear cracked geometries. Specifically, the strain‐hardening behavior typical of soft biological tissues is addressed, and we illustrate its effect on crack‐tip blunting, in terms of a local radius of curvature at the crack tip. A simplified geometrically nonlinear model, proposed to describe the progressive blunting at the crack tip and its effect on flaw tolerance, is validated through finite element analyses and experimental tests on silicone samples. We show how this can lead to a simplified criterion to define the fracture condition in nonlinear soft materials.